The rating of perceived exertion is able to differentiate the post-matches metabolomic profile of elite u-20 soccer players - Marinho, A. H.; Sousa, F. A. D. B.; Vilela, R. D. A. M. P.; Balikian, P.; de Souza Bento, E.; de Mendonça Aquino, T.; Crispim, A.; Ataide-Silva, T.; de Araujo, G. G. (European Journal of Applied Physiology, 2021)
Purpose The study aimed to assess the metabolic impact of elite Brazilian U-20 players using the rating of perceived exertion scale (RPE) to discriminate metabolomics sensitivity post-two soccer games separated by a short recovery interval.